2001
DOI: 10.1111/1467-999x.t01-1-00103
|View full text |Cite
|
Sign up to set email alerts
|

Customer Markets, Inflation and Unemployment in a Dynamic Model with a Range of Equilibria

Abstract: The paper presents a dynamic model incorporating a range of non-accelerating-in¯ation rates of unemployment (NAIRU) obtained according to the theoretical framework proposed by the customer markets literature. The analysis of the dynamic adjustments of unemployment and in¯ation emphasizes the real effects of demand shocks. Changes in the ®scal and monetary policy can exert permanent effects on output and unemployment, both determining persistence in the unemployment rate and selecting the actual steady-state eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To account for a time‐varying NAIRU, several authors have analyzed the role of hysteresis in potential output (Dutt, ; Lavoie, ; Storm & Naastepad, ), while others have suggested that wage and price formation may heavily influenced by ‘endogenous norms’, with a similar result (Arestis & Skott, ; Michl, in press; Skott, ; Stockhammer, ). Other contributions explore the role of customer markets (De Vincenti, ), entry and exit by firms (Ohyama, ) and the employment decisions by employers (Mota, Varejão, & Vasconcelos, ) . The critique of the NAIRU is part of a broader framework where demand shocks have permanent effects on real variables, including a large list of contributions (see e.g., Bruno, ; Commendatore, Panico, & Pinto, ; Cross, ; Fontana & Palacio‐Vera, ; Schoder, , among others).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To account for a time‐varying NAIRU, several authors have analyzed the role of hysteresis in potential output (Dutt, ; Lavoie, ; Storm & Naastepad, ), while others have suggested that wage and price formation may heavily influenced by ‘endogenous norms’, with a similar result (Arestis & Skott, ; Michl, in press; Skott, ; Stockhammer, ). Other contributions explore the role of customer markets (De Vincenti, ), entry and exit by firms (Ohyama, ) and the employment decisions by employers (Mota, Varejão, & Vasconcelos, ) . The critique of the NAIRU is part of a broader framework where demand shocks have permanent effects on real variables, including a large list of contributions (see e.g., Bruno, ; Commendatore, Panico, & Pinto, ; Cross, ; Fontana & Palacio‐Vera, ; Schoder, , among others).…”
Section: Related Literaturementioning
confidence: 99%
“…4 To account for a time-varying NAIRU, several authors have analyzed the role of hysteresis in potential output (Dutt, 2006;Lavoie, 2006;Storm & Naastepad, 2012), while others have suggested that wage and price formation may heavily influenced by 'endogenous norms', with a similar result (Arestis & Skott, 1993;Michl, in press;Skott, 2005;Stockhammer, 2008). Other contributions explore the role of customer markets (De Vincenti, 2001), entry and exit by firms (Ohyama, 1996) and the employment decisions by employers (Mota,4 There are exceptions in the New Consensus literature, for example the insider-outsider models. These models account for the fact that the rate of unemployment seems to meander around without settling at a particular level, and its evolution is better captured from its own past values (Solow, 1990).…”
mentioning
confidence: 99%